Legal Review of Business Dispute Resolution in the Sharia Capital Market - Badruzaman, Dudi; Hermansyah, Yus; Suhara, Djenal; Hasanudin; Rudiansyah, Ahmad (DPPM Universitas Pelita Bangsa, 2023)
An in-depth legal review of dispute resolution mechanisms in the Islamic capital market will ensure that investors' rights are well protected and that there is a clear legal path for investors to seek justice in the event of a dispute. This study aims to analyze the legal position in resolving business disputes in the Sharia capital market. The research method used is library research with a qualitative approach. The results of the study show that the resolution of business disputes in the sharia capital market must always be carried out in compliance with sharia principles and applicable regulations. With appropriate settlement mechanisms, such as Sharia arbitration and mediation and strict supervision from the Sharia Supervisory Board, all parties involved can achieve a fair and beneficial settlement. Compliance with Sharia laws and principles ensures the legality of transactions and increases the trust and integrity of the Sharia capital market.